Causal effect of polyunsaturated fatty acids on bone mineral density and fracture - Tao, Sha-Sha; Wang, Peng; Wang, Xin-Yi; Yin, Kang-Jia; Yang, Xiao-Ke; Wang, Zhi-Xin; Wang, De-Guang; Pan, Hai-Feng (Frontiers in Nutrition, 2022)
Background Polyunsaturated fatty acids (PUFAs) are closely related to osteoporosis. To test their causal relationship, we conducted a Mendelian randomization (MR) analysis. Methods We analyzed the causal relationship between four PUFAs measures, n-3 PUFAs (n-3), n-6 PUFAs (n-6), the ratio of n-3 PUFAs to total fatty acids (n-3 pct) and the ratio of n-6 PUFAs to n-3 PUFAs (n-6 to n-3), and five measures of osteoporosis, including estimated bone mineral density (eBMD), forearm (FA) BMD, femoral neck (FN) BMD, lumbar spine (LS) BMD and fracture, using two-sample MR analysis. Inverse variance weighting (IVW), MR-Egger, weighted and weighted median were conducted. MR-PRESSO and MR-Egger regression methods were used to evaluate the potential pleiotropy of IVs and outliers were identified by MR-PRESSO. Cochran's Q statistic was used to detect the heterogeneity among IVs. Leave-one-out sensitivity analysis was used to find SNPs that have a significant impact on the results. All results were corrected by the Bonferroni correction. Results The IVW results showed that n-3 PUFAs (OR=1.030, 95% CI: 1.013, 1.047, P=0.001) and n-6 PUFAs (OR=1.053, 95% CI: 1.034, 1.072, P<0.001) were positively correlated with eBMD, while n-6 to n-3 (OR=0.947, 95% CI: 0.924, 0.970, P<0.001) were negatively correlated with eBMD. These casual relationships still existed after Bonferroni correction. There were positive effects of n-3 PUFAs on FA BMD (OR=1.090, 95% CI: 1.011, 1.176, P=0.025) and LS BMD (OR=1.056, 95% CI: 1.011, 1.104, P=0.014), n-3 pct on eBMD (OR=1.028, 95% CI: 1.002, 1.055, P=0.035) and FA BMD (OR=1.090, 95% CI: 1.011, 1.174, P=0.025), n-6 to n-3 on LS BMD (OR=1.071, 95% CI: 1.021, 1.124, P=0.005); negative effects of n-3 pct on fracture (OR=0.953, 95% CI: 0.918, 0.988, P=0.009) and n-6 to n-3 on FA BMD (OR=0.910, 95% CI: 0.837, 0.988, P=0.025). However, these causal effects all disappeared after Bonferroni correction (all P>0.0025). Conclusion Evidence from this MR study supports the genetically predicted causal effects of n-3, n-6, n-3 pct and n-6 to n-3 on eBMD. In addition, n-3 not only associate with FA BMD and LS BMD through its own level and n-6 to n-3, but also link to fracture through n-3 pct.